Epoxidation with hydrogen peroxide of unsaturated fatty acid methyl esters over Nb(V)‐silica catalysts. Issue 1 (18th October 2012) - Tiozzo, Cristina; Bisio, Chiara; Carniato, Fabio; Marchese, Leonardo; Gallo, Alessandro; Ravasio, Nicoletta; Psaro, Rinaldo; Guidotti, Matteo
Abstract Niobium(V)‐containing silica catalysts were prepared by deposition of niobocene dichloride onto the surface of high‐surface area silica supports following a dry impregnation or a liquid‐phase grafting approach. These materials were used as heterogeneous catalysts for the selective epoxidation, in the presence of aqueous hydrogen peroxide, of a representative set of unsaturated fatty acid methyl esters (FAME), namely methyl oleate, methyl linoleate, and methyl ricinoleate. They all proved to be water‐tolerant, recyclable, resistant to metal leaching, active and selective in the production of the related epoxidised FAME.